PENGARUH VARIASI VOLUME PADA BIOPLASTIK SARI PATI KENTANG BERPENGUAT SERBUK KAYU JATI TERHADAP KEKUATAN TARIK DAN STRUKTUR MIKRO - Wijaya, Gede Bagus Santika; Kencanawati, Cok Istri Putri Kusuma; Astawa, Ketut (Teknik Desain Mekanika; Vol 13 No 2 (2024): April 2024 : Teknik Desain Mekanik, 2024)
Abstract Many studies have been conducted to reduce the use of synthetic plastics by developing bioplastics from natural polymers such as protein, starch, and bacteria. The great potential of starch in Indonesia encourages opportunities for the development of bioplastics made from starch. This research uses starch from potatoes as the basic material for making bioplastics. As one of the constituent components of biocomposites, powder is used in this study, and the powder used is jati wood powder which is waste from the furniture industry. The composition used in this study is with a volume fraction ratio of 95% potato starch : 5% jati wood powder, 90% potato starch: 10% jati wood powder and 85% potato starch: 15% jati wood powder. The test methods used were tensile tests using ASTM 3039 and micro photographs. In tensile testing, the values of stress, strain and modulus of elasticity were obtained. The average value of tensile stress increased with the highest value at 15% powder volume variation of 3.129 MPa. The highest average tensile strain value was in the 10% powder variation with a value of 1.648. The highest elastic modulus value was found in the 15% variation with an average of 1.431 GPa. Thus it can be concluded that the biocomposite with 15% variation has the highest tensile strength value. Keywords: Bioplastic, Potato Starch, Wood Powder, Volume Variation, Tensile Test, Micro Photograph